1
$\begingroup$

I am looking to find the Legendre polynomial for the following standard Associated Legendre equation:

$$\left(\frac{d}{dx}[1-x^2]\frac{d}{dx}+\lambda-\frac{m^2}{1-x^2}\right)\Theta(x)=0$$

I have found the indicial equation for m=0, but not for m$\neq$0. How do I go about solving this case?

$\endgroup$
1
$\begingroup$

What you can show is that, if $y$ is a solution of $$ \frac{d}{dx}\left((1-x^2)\frac{dy}{dx}\right)+\mu y =0, $$ then $$ w=(1-x^2)^{m/2}\frac{d^my}{dx^m} $$ is a solution of $$ \frac{d}{dx}\left((1-x^2)\frac{dy}{dx}\right)-\frac{m^2}{1-x^2}y+\mu y = 0. \tag{$\dagger$} $$ Therefore, if $P_n(x)$ is the Ordinary Legendre Polynomial, which is the polynomial solution of $((1-x^2)y')'+n(n+1)y=0$, then $$ P_{n,m}(x) = (1-x^2)^{m/2}\frac{d^{m}}{dx^{m}}P_{n}(x) $$ is a solution of the Associated Legendre Equation $(\dagger)$. This holds for a fixed $m$ and for all $n \ge m$ (for $m > n$, the above is identically $0$.) So the Associated Legendre equation has eigenvalues $$ \mu_n=n(n+1),\;\;\; n=m,m+1,m+2,\cdots. $$ For example: $x$ is a solution of the ordinary equation with $\mu=(1)(1+1)=2$. Therefore $$ \sqrt{1-x^2}\frac{d}{dx}x = \sqrt{1-x^2} $$ is a solution of the associated equation with $\mu=(2)(1)$. To check this, $$ \frac{d}{dx}\left((1-x^2)\frac{d}{dx}\sqrt{1-x^2}\right)-\frac{1}{1-x^2}\sqrt{1-x^2} \\ = -\frac{d}{dx}\left((1-x^2)\frac{x}{\sqrt{1-x^2}}\right)-\frac{1^2}{\sqrt{1-x^2}} \\ = -\frac{d}{dx}(x\sqrt{1-x^2})-\frac{1}{\sqrt{1-x^2}} \\ = -\sqrt{1-x^2}+x\frac{x}{\sqrt{1-x^2}}-\frac{1}{\sqrt{1-x^2}} \\ = -\sqrt{1-x^2}+\frac{x^2-1+1}{\sqrt{1-x^2}}-\frac{1}{\sqrt{1-x^2}} \\ = -2\sqrt{1-x^2} $$ Therefore, as expected, $f=\sqrt{1-x^2}$ is a solution of $$ \frac{d}{dx}\left((1-x^2)\frac{df}{dx}\right)-\frac{1^2}{1-x^2}f+(2)(1)f=0. $$ Using the Method of Frobenius: Start by rewriting the equation as $$ \frac{d^2f}{dx^2}-\frac{2x}{1-x^2}\frac{df}{dx}-\frac{m^2}{(1-x^2)^2}f+\frac{\lambda}{1-x^2}f = 0. $$ In order to consider the equation at the singular point $x=-1$, which is a regular singular point, you have to expand in powers of $(x+1)$. For $x=-1$, you only need the coefficients $A$, $B$, $C$ shown below $$ \frac{d^2f}{dx^2}+\left[\frac{A}{x+1}+\cdots\right]\frac{df}{dx}+\left[\frac{B}{(x+1)^2}+\cdots\right]f=0. $$ You can easily determine $A$ and $B$. For example, $$ -\frac{2x}{1-x^2}=\frac{1}{x+1}\left[\frac{2x}{x-1}\right] \implies A = \left.\frac{2x}{x-1}\right|_{x=-1} = 1. \\ -\frac{m^2}{(1-x^2)^2}=\frac{1}{(x+1)^2}\left[-\frac{m^2}{(x-1)^2}\right] \implies B=-\left.\frac{m^2}{(x-1)^2}\right|_{x=-1}=-\frac{m^2}{4}. $$ So the indicial equation comes from solving Euler's equation $$ (x+1)^2f''+A(x+1)f'+Bf = 0,\;\;\; f=(x+1)^r \\ r(r-1)+Ar+B=0 \\ r^2-r+r-\frac{m^2}{4}=0 \\ r^2=\frac{m^2}{2^2} \\ r = \pm \frac{m}{2}. $$ Only the root with the largest real part--in this case $\frac{m}{2}$--is guaranteed to give a solution $(x+1)^{m/2}\sum_{n=0}^{\infty}a_n(x+1)^n$. If you want to take out the singularity at both endpoints $x=\pm 1$, then you can substitute $y=(1-x^2)^{m/2}w$ into the original equation and then solve by a series. In other words, the method of Frobenius leads to the same place in terms of the substitution.

$\endgroup$
6
  • $\begingroup$ I see, this does look really good. Something I forgot to specify though- we need to use the method of Frobenius instead. I have solved the m=0 case, but I am still struggling with the m is not equal to 0 case. Do you know anything further regarding this? Thanks a lot. $\endgroup$ – manuking Dec 29 '16 at 18:42
  • $\begingroup$ @manuking : The method of Frobenius works out the same way, provided you factor out the required factor at both endpoints. But you can work at one endpoint at a time if you want. $\endgroup$ – Disintegrating By Parts Dec 29 '16 at 18:56
  • $\begingroup$ @manuking : I've added more for you concerning the method of Frobenius. $\endgroup$ – Disintegrating By Parts Dec 29 '16 at 19:56
  • $\begingroup$ Thanks for that mate. But it seems that you have lost the lambda along the way? lambda=l(l+1), of course. Any chance you could explain why it's gone please? Thanks a lot! $\endgroup$ – manuking Jan 3 '17 at 15:22
  • $\begingroup$ Ignore that^ I've found out why. I have gone the long way around and come to the same roots as you with the full method of Frobenius expanded- I'm confused on how to implement the next step though. I have been asked to find the first few terms of this series to be specific- do you know how to do this? Any help would be really appreciated. $\endgroup$ – manuking Jan 3 '17 at 16:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.